Stimuli-responsive tertiary amine methacrylate-based block copolymers: Synthesis, supramolecular self-assembly and functional applications - Hu, Jinming; Zhang, Guoying; Ge, Zhishen; Liu, Shiyong (Progress in polymer science, 2014)
In the past decade, responsive polymers exhibiting reversible or irreversible changes in physical properties and/or chemical structures in response to external stimuli have been extensively investigated. Among them, tertiary amine methacrylate-based block copolymers represent a unique category considering their responsiveness to multiple external stimuli (e.g., pH, temperature and salts), which are essentially relevant to the biological milieu. These intriguing properties allow for their applications in a variety of fields ranging from drug or gene delivery, imaging, diagnostics, antibacterial coatings, catalysis, and bio-separations. This review article highlights tertiary amine methacrylate-based block copolymers, focusing on recent advances in the synthesis of tertiary amine methacrylate-based block copolymers with varying chemical structures and chain topologies, their supramolecular self-assembly in aqueous media as well as in the bulk state, and the emerging functional applications.